2019
DOI: 10.2176/nmccrj.cr.2018-0166
|View full text |Cite
|
Sign up to set email alerts
|

Flow Diverter Therapy of a Giant Fusiform Vertebrobasilar Junction Aneurysm in a Child: Case Report

Abstract: The management of giant vertebrobasilar junction (VBJ) aneurysms is extremely challenging. Flow diverter (FD) therapy has become an important alternative to treat difficult intracranial aneurysms for both open surgery and conventional endovascular therapy. Herein, we report a rare case of a giant fusiform VBJ aneurysm in a child that is successfully treated with FD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…In 2018, Oishi et al also reported the results of Pipeline insertion in 94 patients (100 aneurysms); in-stent stenosis developed in one patient. 6) Even when in-stent stenosis is observed after the deployment of Pipeline, it rarely becomes symptomatic, requiring additional treatment. 12) Furthermore, neo-intimal hyperplasia is considered to be an etiological factor for in-stent stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2018, Oishi et al also reported the results of Pipeline insertion in 94 patients (100 aneurysms); in-stent stenosis developed in one patient. 6) Even when in-stent stenosis is observed after the deployment of Pipeline, it rarely becomes symptomatic, requiring additional treatment. 12) Furthermore, neo-intimal hyperplasia is considered to be an etiological factor for in-stent stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…one patient. 6) Even when in-stent stenosis is observed after the deployment of Pipeline, it rarely becomes symptomatic, requiring additional treatment. 12) Furthermore, neo-intimal hyperplasia is considered to be an etiological factor for in-stent stenosis.…”
Section: Journal Of Neuroendovascular Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] Additionally, complex cases can require a combination of FDs with direct surgery and other endovascular methods. [8][9][10] Techniques involve altering the blood flow by occluding vessels before stent placement to transform the aneurysm into a sidewall type, thereby improving occlusion rates. However, few studies have simulated hemodynamic changes in such treatments.…”
mentioning
confidence: 99%